ANALYSIS OF TENSILE STRENGTH, CRYSTALLINITY, CRYSTALLITE SIZE, AND THERMAL STABILITY OF POLYPROPYLENE JOINED BY FRICTION STIR WELDING - Kusharjanta, Bambang; Soenoko, Rudy; Purnowidodo, Anindito; Surya Irawan, Yudy (Journal of Applied Engineering Science, 2021)
This paper aims to investigate the joining of polypropylene using friction stir welding (FSW). FSW parameters were the rotation speed of 620 rpm, the travel speed of 7.3 mm/min, and 13 mm/min. The tensile test was performed using a universal testing machine, and the results of the tensile test were related to the crystallite size and degree of crystallinity. X-ray diffraction (XRD) was performed to examine the crystallite size and degree of crystallinity while thermal analysis was carried out using TGA/DSC. Besides, the effect of the degree of crystallinity on the thermal stability at the weld nugget area due to travel speed is explained in this paper. The findings showed that FSW with a travel speed of 7.3 mm/min had a higher crystallite size and degree of crystallinity than that with a travel speed of 13 mm/min, because there is a fusion of crystals and also recrystallization occurs, as an effect of the difference in the length of time exposed to heat during the FSW process. From the study results, it can be seen that the FSW with a 7.3 mm/minute travel speed has a higher crystal size and degree of crystallinity compare with the use of 13 mm/minute travel speed. The reason for that, the difference in heat exposure time during FSW affects crystal fusion and recrystallization. A sample with a travel speed of 7.3 mm/min had high tensile strength because it obtains sufficient heat for a more complete joint. In terms of thermal stability, the specimen with a lower travel speed showed a higher stability level than the specimen with a higher travel speed in that of the higher degree of crystallinity.